2020
DOI: 10.5021/ad.2020.32.3.233
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report on the Dermoscopic Features of Spark's Nevus

Abstract: Spark's nevus is a compound word composed of Spitz nevus and Clark's nevus. It is one of the combined melanocytic nevi which is more common in female and usually presents as a sharp circumscribed hyperpigmented macule on the lower extremities. On histopathologic findings, both cytologic features of Spitz nevus characterized as large spindle or epithelioid melanocytes containing large nuclei with abundant cytoplasm, and architecture of Clark's nevus characterized as elongation of rete ridges, bridging of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Dermoscopic features of SprkN have been previously described in only few single case reports. Park et al 4 reported a single case that showed brown-to-black globules, diffuse homogenous pigmentation with blue-white structures, brown dots, and isolated eccentric hyperpigmentation. Cimmino et al 3 reported a small series of the lesions characterized by a combined pattern with a central homogeneous blackish and a regular gradient-edged lattice in the peripheries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermoscopic features of SprkN have been previously described in only few single case reports. Park et al 4 reported a single case that showed brown-to-black globules, diffuse homogenous pigmentation with blue-white structures, brown dots, and isolated eccentric hyperpigmentation. Cimmino et al 3 reported a small series of the lesions characterized by a combined pattern with a central homogeneous blackish and a regular gradient-edged lattice in the peripheries.…”
Section: Discussionmentioning
confidence: 99%
“…Dermoscopic features of SprkN in a series of cases have not been described yet; only few single case reports are present in the literature. 2–4 We performed an observational retrospective study at our institution to describe clinical and dermoscopic features of SprkN.…”
Section: Introductionmentioning
confidence: 99%
“…At a 10-year follow-up of 12/27 patients, there were no relapses and/or metastases [ 4 ]. After Fernandez-Flores conducted a careful analysis in 2012 on the eponyms and definitions of less-known nevic lesions [ 11 ], in 2018 and 2020 there were authors [ 12 , 13 ] who tried to define the dermoscopic features of the SPARK nevus. Indeed, although the histological criteria allow a fairly certain definition of this entity, greater difficulties exist when trying to understand which dermoscopic characteristics are peculiar to this type of nevus.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although the histological criteria allow a fairly certain definition of this entity, greater difficulties exist when trying to understand which dermoscopic characteristics are peculiar to this type of nevus. Biondo et al [ 12 ], reporting their clinical case, hypothesized that the dermoscopic pattern was quite similar to that of Clark’s nevus, while in the case of Bin J. et al [ 13 ], the lesion clinically presented as a brownish asymmetrical patch with a diameter of 1 cm at the periphery and a well-demarcated dome-shaped papule that was centrally located: it could not be clearly distinguished from either the Clark nevus or a pigmented Spitz nevus. From the histopathological point of view, it is important to make a correct differential diagnosis with a form of dysplastic nevus with severe atypia or with a melanoma, and a careful cytological evaluation of the melanocytes present at the dermal epidermal junction is absolutely mandatory to correctly diagnose this entity without an over- or underdiagnosis [ 1 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dermatoskopisch sind in der Literatur bisher 2 Fälle von Spark-Nävi mit atypischem Netzwerk, blauem Schleier und peripheren Globuli beschrieben [17,18]. Ja, auch in der histologischen Diagnostik gibt es Grenzen [8][9][10][11]13].…”
Section: Was Ist Ein "Spark-nävus"?unclassified